The Effect of Mental Health First Aid (MHFA) Training on Teachers' Ability to Recognize and Address Bullying Victimization in Elementary Schools - Dewi, Sagung Manik Dwi Purnama; Lestari, Retno; Hariyanti, Tita; Hasan, Haliza (Journal of Nursing Science Update (JNSU), 2025)
The prevalence of bullying is notably highest in elementary schools, which adversely affects children's psychological, physical, and social development. Teachers play a crucial role in supporting students' mental health and must enhance their capacity to identify and address instances of bullying. To this end, implementing a Mental Health First Aid (MHFA) training program is essential. This research aims to evaluate the effectiveness of Mental Health First Aid (MHFA) training courses on teachers' ability to recognize early signs of bullying among elementary school students. Utilizing a quasi-experimental design with a one-group pretest-posttest approach, this study involved 52 participants recruited through purposive sampling. Initial assessments included a pretest consisting of questionnaires measuring cognitive and affective components, along with an observation sheet for psychomotor skills. Following this, participants underwent four sessions of MHFA training, after which a posttest was conducted encompassing cognitive, affective, and psychomotor evaluations. Data analysis was performed using the Wilcoxon test, yielding a p-value of 0.000 (p < 0.05). These results indicate that MHFA training significantly enhances teachers' cognitive, affective, and psychomotor competencies in detecting and addressing bullying victimization in elementary school settings. In conclusion, Mental Health First Aid training has a positive impact on the cognitive, affective, and psychomotor skills of teachers.